Citotaxonomia de Machaerium Pers. e revisão taxonomica de Machaerium Sect. Oblonga (Benth.) Taub. (Leguminosae-Papilionoideae) - Mendonça Filho, Carlos Victor (2002)
Orientadores: Eliana R. Forni Martins, Ana M. G. A. Tozzi